Errors in Indonesian Writing in One Tribun Jabar News Article: A Case Study of Spelling, Punctuation, and Standard Vocabulary - Heni Heryani; Susie Kusumayanthi; Rika Widawati (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study was motivated by the continued occurrence of inaccuracies in Indonesian writing in online news, particularly in the aspects of spelling, punctuation, and standard word usage. Linguistic accuracy in news portals is important because online media not only convey information but also function as models of Indonesian language use in the digital public sphere. This study aims to identify and describe the forms of writing errors found in one selected Tribun Jabar news article, classify the types of errors, and provide corrected forms in accordance with Indonesian language rules. The study employed a descriptive qualitative approach using documentation, close reading, and note-taking techniques. The data were analysed through identification, classification, interpretation, and the formulation of alternative corrections based on the categories of spelling, punctuation, standard word usage, diction, and sentence effectiveness. The findings reveal 18 instances of writing errors. The most dominant errors occur in standard word usage, diction, and sentence effectiveness, with 8 instances (44.45%). Errors in spelling, typing, formatting, and writing consistency account for 6 instances (33.33%), while punctuation and spacing errors account for 4 instances (22.22%). These findings indicate that language problems in online news are not limited to technical inaccuracies but also involve imprecision in word choice and sentence construction. The study implies the need to strengthen journalistic language quality control, particularly in the editing process of online news production, and highlights the value of news texts as authentic materials for Indonesian language learning. However, because the analysis is limited to one selected news article, the findings cannot yet be generalized to the overall language practices of the Tribun Jabar news portal.